General practitioners' knowledge of ageing and attitudes towards older people in China. (9th October 2013) - Yang, Yanni; Xiao, Lily Dongxia; Ullah, Shahid; Deng, Lanlan
<x xml:space="preserve">Abstract</x> Aim To explore general practitioners (GPs)knowledge of ageing, attitudes towards older people and factors affecting their knowledge and attitudes in a Chinese context. Methods Four hundred GPs were surveyed using the Chinese version of the Aging Semantic Differential (CASD) and the Chinese version of the Facts on Aging Quiz (CFAQ1) scale. Results The CASD scores indicated that GPs had a neutral attitude towards older people. The CFAQ1 scores indicated a low level of knowledge about ageing. GPs' awareness of the mental and social facts of ageing was poorer compared to that of physical facts. Male GPs had a significantly higher negative bias score than female GPs. No other variables had a statistically significant influence on knowledge and attitudes. Conclusions The findings suggest the need for education interventions for GPs regarding knowledge of ageing and also provide evidence to guide future development of continuing medical programs for this group of medical doctors.